CYTOKINES PROFILE IN EXPERIMENTAL CONTACT ALLERGIC DERMATITIS AND USE OF NANOENCAPSULATED PREPARATIONS - Khudan-Tsilo, I. I.; Shevchuk, O. O.; Korda, M. M. (International Journal of Medicine and Medical Research, 2018)
Background. Inflammation, oxidative and nitro-oxidative stress are the essentials of the pathogenesis of contact allergic dermatitis as well as cytokines imbalance. Objective. The concentration of TNF-α, IL-1β, IL-4 and IL-10 in blood serum of rats with nickel-induced contact allergic dermatitis was evaluated to determine whether it correlated with the use of free and nanoencapsulated preparations of betamethasone, superoxide dismutase (SOD) and potent highly selective inhibitor of iNOS (1400W). Methods. To induce contact dermatitis (CD), 5 % nickel sulfate was used for 12 days. Experiments were performed on white inbred male rats, 180–220 g of body mass. All rats were divided into 10 groups (n=10). Group I – the control one; II – the animals with CD; III – the rats with CD treated with empty polymeric chitosan nanoparticles; groups IV–VI – the rats with CD treated with free SOD, 1400W and betamethasone; groups VII-IX – the rats administered with nanoencapsulated SOD, 1400W and betamethasone; X – CD + nano-composition of all agents. Results. The statistically higher serum concentrations of TNF-α, IL-1β and decrease of IL-4 and IL-10 in experimental contact dermatitis is proved in comparison with the healthy rats. Mono-treatment with betamethasone, SOD and 1400W is efficient, but the use of nanoparticles loaded with these preparations surpasses its effects. The use of the combination of all nanoencapsulated medicines is the most effective. Conclusions. Chitosan nanoparticles loaded with topical anti-inflammatory glucocorticoid, and inhibitors of oxidative and nitro-oxidative stress is a promising method for treatment of allergic contact dermatitis and can be recommended for further research and use in clinics.